Influence of Non-lethal Doses of Natural Insecticides Spinetoram and Azadirachtin on Helicoverpa punctigera (Native Budworm, Lepidoptera: Noctuidae) Under Laboratory Conditions - Betz, Anja; Andrew, Nigel R. (Frontiers in Physiology, 2020)
Helicoverpa punctigera (native budworm) is an important pest species in Queensland, Western and South Australia. From the third instar onwards, this species causes severe damage to crop plants: therefore, caterpillars need to be managed at an early stage of their development. In our experiment, we raised H. punctigera on an artificial diet, which included different concentrations of the natural insecticides Spinetoram and Azadirachtin. The survival of the larvae, growth and body mass gain was recorded over 17 days. Only caterpillars raised on lowest toxin concentrations survived and moulted successfully to the fifth instar, but had slower growth and body mass gain compared to the control group, which were insecticide-free. Caterpillars fed on higher toxin concentrations never moulted to the next instar or died in the first few days. To test how the toxins influence physiological conditions including metabolic rate and water loss, surviving fifth instar larvae were exposed to thermolimit respirometry: starting at 25 °C following a constant increasing temperature ramping rate of 0.25 °C -1, until reaching the critical thermal maxima (CTmax). The results showed that caterpillars raised on a non-lethal dose of insecticides were differentiating from the control group in their metabolic behaviour and water balance. Insects that have been poisoned seem to consume more energy per mg tissue and have a higher water loss at high temperatures. This study is investigating non-lethal concentrations of insecticides on insects physiology in terms of developmental duration, i.e. growth, moulting and metabolic conditions.